2021
DOI: 10.3390/membranes11020124
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Assessment of Polycaprolactone Membrane on Critical-Size Defects in Rat Calvaria

Abstract: Biomaterials for use in guided bone regeneration (GBR) are constantly being investigated and developed to improve clinical outcomes. The present study aimed to comparatively evaluate the biological performance of different membranes during the bone healing process of 8 mm critical defects in rat calvaria in order to assess their influence on the quality of the newly formed bone. Seventy-two adult male rats were divided into three experimental groups (n = 24) based on the membranes used: the CG—membrane-free co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…From previous study, application of PCL membrane showed bone neoformation, not only at the bone stump but also at the center of the defect in vivo. 10 This osseointegration is well achieved in unmodified PCL scaffold even when compared with nanostructured porous PCL scaffold. \Second, the attachment of the LD muscle to the PCL implant seemed sufficient, resulting in a favorable soft tissue contour with minimal flap sagging.…”
Section: Discussionmentioning
confidence: 86%
“…From previous study, application of PCL membrane showed bone neoformation, not only at the bone stump but also at the center of the defect in vivo. 10 This osseointegration is well achieved in unmodified PCL scaffold even when compared with nanostructured porous PCL scaffold. \Second, the attachment of the LD muscle to the PCL implant seemed sufficient, resulting in a favorable soft tissue contour with minimal flap sagging.…”
Section: Discussionmentioning
confidence: 86%
“…Polycaprolactone (PCL) membrane synthesized by electrospinning technique can mimic the extracellular matrix (ECM), combining both core-shell and nano-reservoirs functionalization [ 81 ]. To promote specific regeneration of the damaged tissues, it is of great use to combine a passive release of anti-inflammatory drugs with nano-reservoir containing pro-regenerative substances.…”
Section: Nano-drug Delivery Systemsmentioning
confidence: 99%
“…Polycaprolactone (PCL) membranes enriched with 5% hydroxyapatite presented good histological results due to the addition of hydroxyapatite and its osteogenic and osteopromotive factors [6]. Interestingly, it induced similar bone healing, which was observed in the control group (BG membranes), showing complete closure of the critical defect.…”
mentioning
confidence: 93%
“…In the field of bone tissue engineering/regeneration, the papers of Bassi et al [5,6] aimed to evaluate the efficiency of different kind of biocompatible and biodegradable membranes in the bone repair of 8-mm critical size defects in rat calvaria. Bacterial cellulose membranes (Nanoskin ® ) (BC) showed interesting properties and presented excellent results in the repair of large soft-tissue injuries [5].…”
mentioning
confidence: 99%